2017
DOI: 10.1111/joss.12260
|View full text |Cite
|
Sign up to set email alerts
|

Influence of packaging and product information on consumer perception of cosmetic creams—A case study

Abstract: The influence of packaging and packaging elements on consumer perception of cosmetic creams was studied. Two groups, each consisting of 100 respondents, rated five face skin care creams (one of which was imported) and evaluated the unpackaged and the packaged product, respectively. Respondents rated each sample in terms of overall liking and provided a description of sample attributes by means of a check‐all‐that‐apply (CATA) question. Packaging elements like product composition, product information, and brand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…Natural packaging also refers to the design process of the product package, such as using raw materials and colors that stimulate the consumers' senses and affect their purchase intention (Wang et al, 2022; Kobayashi & Benassi, 2015). Package printed information (PPI) refers to the labeling and logo position and design on the products packages (Shukla, Misra, & Singh, 2022; Sousa, Carvalho, & Pereira, 2020; Gámbaro, Roascio, Boinbaser, & Parente, 2017). The SC on natural skincare products' packaging indicates the provision of a particular SC, or safety logo on products labeling to show the products safety indicators (Ngo, Liu, Moritaka, & Fukuda, 2021).…”
Section: Background Literaturementioning
confidence: 99%
“…Natural packaging also refers to the design process of the product package, such as using raw materials and colors that stimulate the consumers' senses and affect their purchase intention (Wang et al, 2022; Kobayashi & Benassi, 2015). Package printed information (PPI) refers to the labeling and logo position and design on the products packages (Shukla, Misra, & Singh, 2022; Sousa, Carvalho, & Pereira, 2020; Gámbaro, Roascio, Boinbaser, & Parente, 2017). The SC on natural skincare products' packaging indicates the provision of a particular SC, or safety logo on products labeling to show the products safety indicators (Ngo, Liu, Moritaka, & Fukuda, 2021).…”
Section: Background Literaturementioning
confidence: 99%
“…Italians prefer transparent bottles and Dutch prefer dark bottles. Gámbaro, Roascio, Boinbaser, and Parente () also support the stimulating effect of packaging on the perception of consumers of cosmetic creams. The packaging elements like product composition, product information, and brand image influenced both overall liking ratings and the choice of attributes used by respondents to describe the samples.…”
Section: Introductionmentioning
confidence: 80%
“…Data gathering Documents, papers, interviews, and survey reports were used to research the issues related to the sunscreen category, problems and conditions with the skin labels and packaging for sunscreen and exploring the behavior and demands for augmented reality technologies through the use of Augmented Reality. A survey of 30 face sunscreen purchasers' behaviors and demands for augmented reality technology to get facial sunscreen product label information via a mobile application revealed that: In the case of facial sunscreens, 96.7 percent are concerned about the components and would like to use augmented reality technology to get face sunscreen label information via a user's mobile application [2], [3].…”
Section: Methodsmentioning
confidence: 99%
“…The product label information on the container is written in a small font that is difficult to see, this may cause customers to select a sunscreen that is inappropriate for their skin type [3], [6]. As a result, the researchers devised a strategy to make it easier for consumers to obtain information on packaging.…”
Section: Introductionmentioning
confidence: 99%